Penyuluhan Pencegahan Pernikahan Dini pada Usia Remaja di Sekolah Menengah Pertama - Rosa Desmawanti; Akmaluddin (TAAWUN, 2023)
This service aims to provide education as an effort to prevent early marriage at a young age for students at SMP Negeri 4 Selong, East Lombok. This service is carried out using the Participatory Action Research (PAR) method with the following stages: (1) initial mapping, (2) building communication with teachers and students, (3) determining service topics and mapping problems, (5) compiling technical activities, ( 6) carry out community service activities, (7) form discussion groups, (8) reflect. The results of the participant satisfaction survey for this community service activity showed very positive results. One of them is shown by the number of questions asked by the participants, related to the material presented. In addition, the participants also shared their personal experiences with those closest to them who were under direct pressure from their parents to marry early. The satisfaction of the participants was also inseparable from the speakers presented who were competent and focused on social issues, humble in nature so that they could place themselves well in the midst of teenage students.